Advancing citizen-centered public services in Kazakhstan: legal, institutional, and digital governance perspectives - Amirova, Aigerim (Frontiers in Political Science, 2025)
Digital transformation of public services is reshaping governance worldwide, yet evidence on citizen-centered outcomes in emerging economies remains limited. Kazakhstan’s ambition to adopt proactive, composite, and once-only service models presents an opportunity to evaluate how far institutional intent translates into improved citizen experience. We used a mixed-methods design combining (i) SWOT and PEST analyses of legal, institutional, and technological frameworks; (ii) an expert panel (n = 5 senior staff of the Agency for Civil Service Affairs, rating 7 items on a 0–5 scale); (iii) a large-scale national e-government survey of 27,336 authenticated respondents across all 20 regions (completion rate 97.1%); and (iv) international focus groups on AI in public services. Weighted percentages and Wilson 95% confidence intervals were calculated for citizen-reported problems; expert mean ratings summarized institutional factors. Experts rated enforcement capacity (mean 4.8/5) and statutory basis for once-only/composite/proactive services (4.6/5) highest among political factors, but identified weak international financial support (3.4/5) and cybersecurity posture (3.8/5) as persistent gaps. Citizen survey data show technical errors (23.3, 95% CI 22.8–23.8), redundant bureaucracy (15.2%, 14.8–15.7), and staff capability gaps (14.5%, 14.0–14.9) as the leading obstacles. Urban respondents were overrepresented (98.4% vs. 1.6% rural), highlighting a digital inclusion gap. Focus groups found that 70.8% of international participants reported some use of AI in public services but noted uneven environmental safeguards. Kazakhstan has built a robust legal and institutional infrastructure for digital public services, yet legacy registers, digital divides, and data-protection gaps constrain performance. Codifying once-only, composite, and proactive services as mandatory principles, investing in data stewardship and cybersecurity, and treating inclusive digital literacy as public infrastructure are critical next steps. These findings offer a model for other emerging economies seeking to balance innovation with equity and accountability.